AKTIVITAS FISIK DENGAN KEJADIAN INSOMNIA PADA ATLIT GYM - Manggopa, Rafli; Kundre, Rina; Katuuk, Mario (JURNAL KEPERAWATAN, 2019)
Abstract : Insomnia is a difficulty in starting and maintaining sleep so someone cannot meetadequate sleep needs, both quantity and quality. Physical activity is a body movement producedby skeletal muscle which results in energy expenditure, regular physical activity has long beenconsidered an important component in healthy living. The purpose of this study was todetermine the relationship between physical activities and the incidence of insomniaexperienced by Manado Global gym athletes. The research method used was observationalanalytic with cross sectional design. The sampling technique in this study was total samplingwith 100 samples. Data collection is done using a questionnaire. The research result based onstatistic test of Chi-Square test with the level of meaning 95% (Î± = 0,05) is presented on a table2x3 with earned value Ñ€ = 0,000 which is smaller than Î± (0,05) with rejected Ho and acceptedHa. The conclusion shows that there is a correlation between physical activities and insomniacondition experienced by Global Manado gym athletes.Keywords : Physical activity, insomnia incidentAbstrak : Insomnia merupakan kesukaran dalam memulai dan mempertahankan tidur sehinggatidak dapat memenuhi kebutuhan tidur yang adekuat, baik kuantitas maupun kualitas. Aktivitasfisik merupakan gerakan tubuh yang dihasilkan oleh otot rangka yang mengakibatkanpengeluaran energi, aktivitas fisik secara teratur telah lama dianggap sebagai komponen pentingdalam hidup sehat. Tujuan penelitian ini untuk mengetahui hubungan aktivitas fisik dengankejadian insomnia pada atlit gym Global Manado. Metode penelitian yang digunakan yaituobservasional analitik dengan rancangan cross sectional. Teknik pengambilan sampel padapenelitian ini yaitu total sampling dengan jumlah 100 sampel. Pengumpulan data dilakukanmenggunakan kuesioner. Hasil penelitian berdasarkan uji statistik Chi-Square test dengantingkat kemaknaan 95% (Î± = 0,05) disajikan dalam tabel 2x3 diperoleh nilai Ñ€ = 0,000 yaknilebih kecil dibandingkan Î± (0,05) dengan Ho ditolak dan Ha diterima. Kesimpulan terdapathubungan aktivitas fisik dengan kejadian insomnia pada atlit gym Global Manado.Kata kunci : Aktivitas fisik, Kejadian Insomnia